Trials by Peers: The Ebb and Flow of the Criminal Jury in France and Belgium - Germain, Claire M. (2018)
The participation of lay jurors in criminal courts has known much ebb and flow both in France and in Belgium. These two countries belong to the civil law tradition, where juries are the exception rather than the rule in criminal trials, and they only exist in criminal cases, not civil cases. In spite of some similarities, there are substantial differences between the two countries, and their systems will be examined in turn. In France, the Cour d’assises itself was inherited from the French Revolution. Since a law of 1941, it is a mixed jury system, meaning that lay citizens sit together with professional judges, The Cour adjudicates severe crimes only, mostly rapes and murders. A pilot program extended lay participation to criminal courts beyond the Cour d’assises, but was stopped and resulted in the reduction of the number of lay citizens on the Cour d’assises. In Belgium, the institution of the criminal jury in the Cour d’assises is enshrined in the Belgian Constitution. Up until 2016, it functioned as a “true” jury, in the sense that only lay citizens sat on the jury, without the participation of professional judges. A 2016 reform allowed for the reclassification of crimes into lesser offenses within the competence of the criminal courts, with very few exceptions. Additionally, from February 2016 on, judges deliberate with lay citizens on the guilt of the accused. The paper will explain the reasons for these changes and evolution of the participation of lay citizens in the criminal jury in France and Belgium, and include a few remarks about the future for lay participation in these two countries, since there are several current proposals on the table, both in France and in Belgium